Roles of Supplementary Motor Areas in Auditory Processing and Auditory Imagery. - Lima, C; Krishnan, S; Scott, S (Cell Press, 2016)
Although the supplementary and pre-supplementary motor areas have been intensely investigated in relation to their motor functions, they are also consistently reported in studies of auditory processing and auditory imagery. This involvement is commonly overlooked, in contrast to lateral premotor and inferior prefrontal areas. We argue here for the engagement of supplementary motor areas across a variety of sound categories, including speech, vocalizations, and music, and we discuss how our understanding of auditory processes in these regions relate to findings and hypotheses from the motor literature. We suggest that supplementary and pre-supplementary motor areas play a role in facilitating spontaneous motor responses to sound, and in supporting a flexible engagement of sensorimotor processes to enable imagery and to guide auditory perception.